Types and frequency of ovarian masses in children over a 10-year period - Sadeghian, Naser (Caspian J Intern Med, 2015)
BACKGROUND: Ovarian masses represent a range of pathology from benign cyst to highly aggressive malignant tumors. It has been estimated that gynecologic malignancy account for approximately 2% of all types of cancer in children, 60-70% of these lesions arise in the ovary. METHODS: All ovarian masses which were resected or biopsied in Mofid Children's Hospital from 2002 to 2012 were reviewed retrospectively. Patient’s age, presenting symptoms, surgical procedures, pathological diagnosis, postoperative treatment, and outcome were obtained from medical records. RESULTS: Fifty-seven girls (aged 40.2±57months with the range of 1 day to 15 years) underwent different types of ovarian operations (24 salpingo-oophorectomies, 10 oophorectomies, 21 ovarian cystectomies, and 2 ovarian biopsies). 50 children had unilateral ovarian mass (49.1% right and 38.6 left, respectively). The most common presenting symptoms were acute abdominal pain in 46%.Twenty one (37%) of our patients had ovarian torsion. Four (7%) patients had benign tumors, and 8 (14%) had malignant tumors. There were no age differences between those with benign type (8.2±2.6years) and malignant tumors (6.1±5.3years) (P=0.683). CONCLUSION: Ovarian tumors are rare in children. Most are benign, in children presenting with acute abdominal pain, ovarian mass particularly neoplastic tumors should be suspected. An important proportion of these patients may require postoperative chemotherapy.